The Closing of China? Possible Implications for Universities Worldwide - Altbach, Philip; de Wit, Hans (International Higher Education, 2018)
Experts have noted that president Xi has amassed the most power since Mao Zedong, and seeks long-term authority to carry out his policies. This article examines the possible impacts on higher education -- especially the internationalization of higher education -- in China and beyond.